Gold Price Dynamics and the Role of Uncertainty - Joscha Beckmann; Theo Berger; Robert Czudaj (Chemnitz University of Technology, Faculty of Economics and Business Administration, 2017)
This study adopts a copula wavelet approach to analyze dynamics of the gold price against bonds, stocks and exchange rates based on disaggregation of the underlying relationships across different frequencies. We also examine whether gold prices are directly affected by changes in uncertainty. Analyzing data for nine economies for a sample period starting in 1985, we find that the role of gold changes significantly after the collapse of Lehman Brothers in 2008. Gold is unable to serve as a hedge in the classical sense while the findings for the period prior to 2008 mostly suggest that gold is able to shield investors. Uncertainty measures display a surprising and time-varying relationship with the path of the gold price. While economic policy uncertainty is positively correlated with gold price developments, macroeconomic uncertainty and inflation uncertainty among forecasters are both negatively related to gold.
Keywords: G11; G15; C58; 330; bonds; exchange rates; gold; hedge; safe haven; stocks; uncertainty